Guaraná (Paullinia cupana) seeds: Selective supercritical extraction of phenolic compounds. (1st December 2016) - Marques, Leila Larisa Medeiros; Panizzon, Gean Pier; Aguiar, Bruna Aparecida Alves; Simionato, Ane Stéfano; Cardozo-Filho, Lucio; Andrade, Galdino; de Oliveira, Admilton Gonçalves; Guedes, Terezinha Aparecida; Mello, João Carlos Palazzo de
Highlights: The addition of modifiers improves the extraction of polar compounds by SFE. The percentage of modifier used is directly proportional to the amount of TPC. The temperature had a significant effect on TPC, followed by the modifier. The amount of caffeine extracted decreases with increasing proportions of modifier. The best condition for polyphenols: 40% of modifiers, 40 min, 40 °C, and 100 bar. Abstract: Approximately 70% of the Brazilian production of guaraná ( Paullinia cupana ) seeds is absorbed by the beverage industries. Guaraná has several pharmacological properties: energy stimulant, antimicrobial, chemoprophylactic, antigenotoxic, antidepressive, anxiolytic, and anti-amnesic effects. Supercritical carbon dioxide extraction of bioactive compounds from guaraná seeds was carried out and optimized by an orthogonal array design (OA9 (3 4 )). The factors/levels studied were: modifier(s) (ethanol and/or methanol), extraction time (20, 40, and 60 min), temperature (40, 50, and 60 °C), and pressure (100, 200, and 300 bar). The statistical design was repeated with increasing proportions of modifiers. The percentage of modifier used was proportional to the amount of polar compounds extracted. The best conditions for the supercritical extraction, based on the content of polyphenols, epicatechin/catechin quantification, yield and operating cost, proved to be: 40% ethanol:methanol during 40 min, under 40 °C, and 100 bar. The temperature had a significant effect on the total phenolic content.